Adsorption studies of dyeing natural dyes from local resources onto bamboo yarn - Tengku Khamanur Azma, Tg. Mohd Zamri (2017)
Recently, natural dyes play an important role in the textile industry due to the needs of substituting synthetic dyes that are deleterious to the environment. This means; the use of natural dyes does benefits their entire user which attribute in numerous industries, such as textiles, leather, paper, and plastics, to colour their final products. Effluents from such industries are major sources of water pollution. Hence, it is important to find alternative to replacing the synthetic dyes as well as synthetic fibers by promoting the simple, efficient, and inexpensive ways to extract the natural dyes and dyeing it onto bamboo yarn (BY). This research is navigated by four prime objectives, in which the first objective is to optimize the extraction of selected natural dyes from local resources. The second objective is to optimize the dyeing of natural dyes on the BY. These optimizations were done via OFAT and central composite design (CCD) in RSM with the aid of Design Expert Version 8.0.6. The selected natural dyes were extracted from Blue Butterfly Pea Flower (BBPF), Red Dragon Fruit Peel (RDFP), and Turmeric. Meanwhile, the third objective is to evaluate the dyeing adsorption kinetically and adsorption isotherm between colorant pigments extracted from selected natural dyes onto BY. The adsorption of natural dyes on BY had been studied with the application of Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherm models. The kinetic studies of dyeing natural dyes onto BY were investigated by using Pseudo-first order model and Pseudo-second order model. Finally, the last objective is to characterize the colorant pigments extracted from selected natural dyes, undyed and dyed yarns which are BY through the analyses of FTIR spectroscopy and SEM. As a result, this study had determined that the optimum extraction of BBPF dye for temperature, time, and SLR are 55 °C, 15 minutes and 0.10 g/mL, respectively; while turmeric dye extraction at 55 °C, 25 minutes and 0.12 g/mL, respectively. Other than that, the optimum conditions of dyeing BY with BBPF dye for dye bath concentration, dyeing time, and dye bath pH had been 0.083 g/mL, 60 minutes and 6.5, respectively. On the other hand, the optimized conditions of dyeing of RDFP dye and turmeric dye on BY for dye bath concentration, dyeing time, dye bath pH, and dyeing temperature were 0.10 g/mL and 0.101 g/mL, 90 minutes and 60 minutes, pH 3 and pH 4.1, 70 °C and 67 °C, respectively. In addition, the data retrieved from the experimental runs displayed a good linear fit, as reflected from the pseudo-first order kinetic model for adsorption of anthocyanin in BBPF dye onto BY. Furthermore, pseudo-second order kinetic model had been fit for the adsorption of the colorant pigments of betacyanin (RDFP) and curcumin (turmeric) onto BY. Meanwhile, Langmuir isotherm was fit only for betacyanin adsorption onto BY, whereas Freundlich isotherm and Temkin isotherm for anthocyanin and curcumin adsorption onto BY respectively. Based on the results of the best isotherm model and kinetic model, the dyeing of BBPF dye on BY was controlled by physical adsorption while dyeing of RDFP dye and turmeric dye on BY were both controlled by chemisorption. FTIR analysis showed that the selected natural dyes were formed weak bonds on BY, resulting in minimal chemical changes. As a conclusion, all the objectives outlined in this study have been successfully achieved and all natural dyes that were selected in this study were compatible with BY.